Music Performance Anxiety in Higher Music Education: A Narrative Review of Mechanisms, Assessment, and Pedagogical Intervention - Wang, Peiyong; Seungjin, Lee (Journal of Educational Research and Policies, 2026)
Music performance anxiety (MPA) is a persistent and often disabling form of anxiety that emerges in situations where musical performance is observed, judged, recorded, or formally assessed. Although mild arousal can support concentration and expressive energy, maladaptive MPA may disrupt attention, memory retrieval, fine motor control, musical communication, and long-term professional identity. This narrative review synthesizes major theoretical, assessment, and intervention literature on MPA, with a particular focus on higher music education and implications for Chinese music students. Targeted searches of PubMed, publisher websites, and reference lists were conducted to identify peer-reviewed systematic reviews, conceptual papers, psychometric studies, and intervention studies published up to May 2026. The review argues that MPA should not be reduced to ordinary stage fright or temporary nervousness. It is better understood as an interaction among biological vulnerability, trait anxiety, cognitive appraisal, perfectionism, self-focused attention, previous performance experiences, and social-evaluative educational environments. The Kenny Music Performance Anxiety Inventory and related performance-specific measures provide useful assessment tools, but intervention planning should combine self-report scales with performance observation, contextual interviews, and, where appropriate, physiological indicators. Evidence supports the promise of cognitive-behavioral strategies, graded exposure, acceptance and commitment approaches, mental skills training, relaxation, mindfulness, biofeedback, and music therapy-informed methods, but current intervention research remains limited by small samples, heterogeneous protocols, and insufficient follow-up. For international music education, the most defensible direction is not a single universal treatment but a mechanism-informed, curriculum-embedded support model that links assessment, psychological skills, performance practice, and pedagogical feedback.